Uniportal VATS Approach in Esophageal Cancer – How to Do It Update - Batirel, Hasan (Frontiers in Surgery, 2022)
Adoption of minimally invasive esophagectomy has taken over a decade and chest part is evolving into a uniportal videothoracoscopic approach. Uniportal esophageal mobilization and anastomosis have many peculiar aspects which include placement of incision, alignment of instruments and anastomosis. The incision is placed over the 6th intercostal space posterior axillary line. Esophagus is usually encircled at the level of inferior pulmonary vein. Use of a curved suction helps in retraction of esophagus and exposure of left main bronchus deep in the mediastinum. For intrathoracic anastomosis in Ivor Lewis esophagectomy a completely stapled side to side linear stapled anastomosis is preferred. This anastomotic technique results in a long stapler line. Correct alignment of tissues as well as adequate anastomotic circumference are utmost importance to prevent leak or strictures. Perioperative and oncologic results in several series with uniportal videothoracoscopic esophageal mobilization and anatomosis are comparable with open or other types of minimally invasive esophagectomy. Uniportal videothoracoscopic esophagectomy is feasible and fast with good results.